Eccrine Angiomatous Hamartoma: A Clinicopathologic Review of 18 Cases. (June 2016) - Patterson, Andrew T.; Kumar, Monique G.; Bayliss, Susan J.; Witman, Patricia M.; Dehner, Louis P.; Gru, Alejandro A.
Abstract : Background: Eccrine angiomatous hamartoma (EAH) is a benign cutaneous lesion defined by the proliferation of hamartomatous eccrine and capillary-like vascular elements in the dermis. However, the epidemiologic, morphologic, and histopathologic aspects of this uncommon disorder have yet to be fully delineated. Methods: The authors retrospectively reviewed 18 EAH cases (including 14 accompanying skin biopsy specimens) diagnosed at 4 American university hospitals from 1996 to 2014. Results: Patients ranged from 3 days to 84 years at time of diagnosis with a median age of 15 years. A male:female ratio of 11:7 was observed. Sixty-seven percent of cases presented in the extremities, but lesions in the trunk and head/neck regions also occurred. Four patients had multiple lesions, and 2 displayed a segmental pattern. Histologically, dermal vascular dilatation and acanthosis often accompanied EAH's typical eccrine and vascular comingling. One individual developed EAH at the site of a recurrent squamous cell carcinoma after previous excision. Conclusions: Although previously thought to occur primarily as a solitary angiomatous-appearing malformation on the extremities of children, EAH may develop with some frequency in adults and may manifest in a multifocal linear distribution. The authors also raise additional histopathologic consideration in support of the vascular theory of histogenesis for this condition.